Do democratic revolutions 'activate' participants? The case of Tunisia. (May 2020) - Doherty, David; Schraeder, Peter J; Dobbs, Kirstie L
The democratic transition in Tunisia and free and fair elections that followed offer a unique opportunity to assess whether the experience of participating in successful political efforts translates into subsequent political participation. We consider whether participation in a democratic revolution is associated with greater rates of participation in nascent 'normal' democratic processes. Leveraging data from two surveys fielded in the wake of the revolution and the Constituent Assembly elections that followed, we find scant evidence of a relationship between protest participation and subsequent turnout. We also consider the possibility that young – presumably more impressionable – Tunisians were more likely to be 'activated' by protest participation. However, our findings run directly counter to this expectation. Our findings show that the socializing effects of monumental historical events can be strikingly circumscribed.